Ski economy and physiological responses while double poling - curved vs. straight poles - Mishica, C.; Ohtonen, O.; Leppävuori, A.; Linnamo, V. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Double poling (DP) is commonly used in cross country skiing (XC) (1). It is becoming more and more popular and in some competitions it is the exclusive technique. Ski poles allow a skier to apply power and force to the snow and their composition and design have a significant effect on performance. Different pole lengths and cross sections are some of the differences that have been tested. Advancements in equipment will continue to be introduced so it is important to have research that supports the possible benefits and physiological reasoning behind these changes. The purpose of this study was to investigate and compare ski economy and physiological responses in XC skiing while performing the DP technique with curved and straight ski poles.